A competency-based model of the human resource development management of ustadz at salaf boarding school. Issue 5 (8th June 2015) - Uhbiyati, Nur
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to study the criteria of qualified ustadz and how the salaf boarding school leader (kyai) manages the ustadz in order for them to become qualified ustadz. Design/methodology/approach – This study uses a qualitative research approach. Data were collected by in-depth interview techniques with kyai and mentor as primary source of data, while participants and alumni as secondary ones. The correctness of data from kyai and mentor then were cross-checked against data from participants and alumni. Findings – This paper gives the following findings: the qualified ustadz is ustadz who has competencies of personal religious, professional religious, social religious, and life skills; while efforts undertaken by kyai are planning, organizing, implementation and evaluation. Originality/value – The paper contributes to the Islamic educational institution in development management model for ustadz that has some stages, namely: need analysis, planning design, implementation and development evaluation. The proposed model can be used as a reference for leader of traditional Islamic education around the world in order to improve the quality of ustadz.